Análise de desempenho do emprego do multi-acesso em redes compostas por sistema celular de terceira geração e rede local sem fio - Cardoso, Leonardo Sampaio (2006)
With the increasing demands for data services over the cellular networks, their operators are faced with the issue of providing the requested capacities while maintaining the service quality levels. The Multi-Access (MA) networks can be a cost effective way of raising those capacities, as it provides means to aggregate radio resources from the adopted Radio Access technologies (RATs) involved. Although the MA concept seems very promising, the gains concerning its adoption are not quite clear. These gains can come from different sources, such as from the inclusion of a second RAT itself and from the adoption of a suitable Access Selection (AS) procedure. The former concerns the gains available with the increase in the amount of radio resources while the latter concerns the ones available with a more suitable distribution of users among the RATs. This work aims to clarify the gains concerning the usage of the WLAN IEEE 802.11a in addition to the UTRAN, both in the homogeneous user distribution and hotspot cases, while employing the MA framework as the enabling technology. It also looks into the characteristics of some AS procedures based on coverage, user bit rate, estimated RAT throughput and mixed (user bit rate and load), aiming at clarifying which ones provide the best performance. The evaluation is based on a dynamic system-level multi-access simulator, comprised of a good and detailed level of the modeling concerning the involved technologies and concepts. Results show that considering the assumptions and modeling, significant capacity gains can be achieved when using intelligent AS algorithms in the UTRAN-WLAN MA networks.